2010
DOI: 10.1038/ismej.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

High bicarbonate assimilation in the dark by Arctic bacteria

Abstract: Although both autotrophic and heterotrophic microorganisms incorporate CO 2 in the dark through different metabolic pathways, this process has usually been disregarded in oxic marine environments. We studied the significance and mediators of dark bicarbonate assimilation in dilution cultures inoculated with winter Arctic seawater. At stationary phase, bicarbonate incorporation rates were high (0.5-2.5 lg C L À1 d À1 ) and correlated with rates of bacterial heterotrophic production, suggesting that most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 47 publications
11
122
0
4
Order By: Relevance
“…The nitrite-oxidizing genus Nitrospina has been observed in winter-only samples from both Antarctic (Grzymski et al, 2012) and Arctic (Alonso-Sáez et al, 2010) waters, as well as in temperate waters (El-Swais et al, 2015) and has also been correlated with amoA-containing Thaumarchaeota in Monterey Bay (Mincer et al, 2007). Whilst we recorded generally higher levels of all three taxa in winter surface and year-round deeper waters, active populations were still detected in surface waters in summer months, albeit at much lower levels.…”
Section: Discussionmentioning
confidence: 64%
“…The nitrite-oxidizing genus Nitrospina has been observed in winter-only samples from both Antarctic (Grzymski et al, 2012) and Arctic (Alonso-Sáez et al, 2010) waters, as well as in temperate waters (El-Swais et al, 2015) and has also been correlated with amoA-containing Thaumarchaeota in Monterey Bay (Mincer et al, 2007). Whilst we recorded generally higher levels of all three taxa in winter surface and year-round deeper waters, active populations were still detected in surface waters in summer months, albeit at much lower levels.…”
Section: Discussionmentioning
confidence: 64%
“…Carnivorous and detritus feeding by zooplankton could also have supplied labile dissolved compounds to the bacteria prior to the spring primary production, as indicated by the significant correlation between bacterial production and zooplankton production (Forest et al 2011). In addition, a recent study showed that other phylogenetically diverse psychrophylic strains of arctic bacteria are able to directly assimilate CO 2 in dark and nutrient-deprived winter conditions (Alonso-Saez et al 2010) presumably from the exploitation of metabolic processes such as nitrification (Galand et al 2009b). This high flexibility in the use of labile to refractory organic compounds at a time of low and extremely variable food availability is certainly the key to the maintenance of an active microbial food web throughout winter.…”
Section: The Winter Microbial Food Webmentioning
confidence: 99%
“…Although light-independent or dark CO 2 assimilation has been usually assumed to be insignificant in oxygenated marine waters, a recent work by Alonso-Sáez et al (2010) suggests that the global relevance of this process could have been underestimated. Those results show for the first time that high ambient CO 2 concentrations could stimulate CO 2 fixation rates by increasing the CO 2 flux into the cells.…”
Section: Abstract: Bacterial Metabolism · Flavobacteriaceae · Ocean mentioning
confidence: 99%